Carotenoids, carotenoid esters, and anthocyanins of yellow-, orange-, and red-peeled cashew apples (Anacardium occidentale L.). (1st June 2016) - Schweiggert, Ralf M.; Vargas, Ester; Conrad, Jürgen; Hempel, Judith; Gras, Claudia C.; Ziegler, Jochen U.; Mayer, Angelika; Jiménez, Víctor; Esquivel, Patricia; Carle, Reinhold
Highlights: Yellow and orange color of cashew apples was due to at least 15 carotenoids. Red peels additionally contained characteristic anthocyanins. β-Carotene and β-cryptoxanthin palmitate were major carotenoids in all samples. Several minor β-cryptoxanthin, lutein, and zeaxanthin esters were detected. Orange-fleshed cashew apples represent a good source of provitamin A carotenoids. Abstract: Pigment profiles of yellow-, orange-, and red-peeled cashew ( Anacardium occidentale L.) apples were investigated. Among 15 identified carotenoids and carotenoid esters, β-carotene, and β-cryptoxanthin palmitate were the most abundant in peels and pulp of all samples. Total carotenoid concentrations in the pulp of yellow- and red-peeled cashew apples were low (0.69–0.73 mg/100 g FW) compared to that of orange-peeled samples (2.2 mg/100 g FW). The color difference between the equally carotenoid-rich yellow and red colored samples indicated the presence of a further non-carotenoid pigment type in red peels. Among four detected anthocyanins, the major anthocyanin was unambiguously identified as 7- O -methylcyanidin 3- O -β-d -galactopyranoside by NMR spectroscopy. Red and yellow peel color was chiefly determined by the presence and absence of anthocyanins, respectively, while the orange appearance of the peel was mainly caused by increased carotenoid concentrations. Thus, orange-peeled fruits represent a rich source of provitamin A (ca. 124 μg retinol-activity-equivalents/100 g pulp, FW).